If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6/3x+4/6x=28/9
We move all terms to the left:
6/3x+4/6x-(28/9)=0
Domain of the equation: 3x!=0
x!=0/3
x!=0
x∈R
Domain of the equation: 6x!=0We add all the numbers together, and all the variables
x!=0/6
x!=0
x∈R
6/3x+4/6x-(+28/9)=0
We get rid of parentheses
6/3x+4/6x-28/9=0
We calculate fractions
(-3024x^2)/1458x^2+2916x/1458x^2+972x/1458x^2=0
We multiply all the terms by the denominator
(-3024x^2)+2916x+972x=0
We add all the numbers together, and all the variables
(-3024x^2)+3888x=0
We get rid of parentheses
-3024x^2+3888x=0
a = -3024; b = 3888; c = 0;
Δ = b2-4ac
Δ = 38882-4·(-3024)·0
Δ = 15116544
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:x_{1}=\frac{-b-\sqrt{\Delta}}{2a}x_{2}=\frac{-b+\sqrt{\Delta}}{2a}\sqrt{\Delta}=\sqrt{15116544}=3888x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(3888)-3888}{2*-3024}=\frac{-7776}{-6048} =1+2/7x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(3888)+3888}{2*-3024}=\frac{0}{-6048} =0
| 29=3s-4(26-s) | | 14-5n=6(n+6) | | 9=7+v | | -20j-(-14j)+2j=20 | | 90=6x+3 | | 6x+10=3x+26 | | 18p-12p-p-3p=10 | | 60-1/2x=10 | | 6x-20=9x-110 | | x=3x^2-7x-2 | | 4+6x=110 | | 540=35x+40 | | 110=4+6x | | (x+3)^2=-2x | | x^2=56-12x | | B3-8b2+16b=0 | | −5x−3=−7(x−1) | | 15x-3=13x+11 | | -24=-6d | | 4/3(2+m)-7/3(-3-m)+4/3(4+m)-3-3m=0 | | 5(x+100)=450 | | r+12=16 | | 7x−4=6x+5 | | 6(x-4)=3x-24= | | 4x+3=8x−5 | | 1/3y+11=1/2y+3 | | 8x+13=30 | | 1*b=b-8 | | 2p4+25=29 | | 2(5-2y))=35-9y | | 2(9)=p | | 4(12)=g |